Modes of criticism 4 : Radical pedagogy - Abdulla, Danah; Willis, Anne-Marie; Ahmed, Tanveer; FitzGerald, Kenneth; Groten, Anja; Ellis, Hannah; Laranjo, Francisco, 1955- (Eindhoven : Onomatopee, 2019)
This volume investigates the use of the word 'radical' in design discourse and practice, tracing precedents, problems and challenges for the future of the discipline. Table of contents: Radicalise Me / Danah Abdulla. Ontological Design and Criticality / Anne-Marie Willis. Anti-Fashion: using the sari to decolonise fashion / Tanveer Ahmed. (Incomplete) / Kenneth FitzGerald. Working From Within: depatriarchise design. Design Friction / Anja Groten. Education at 400bpm / Hannah Ellis.
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek
Keywords: Design -- Political aspects; Design -- Political aspects